The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/antibiotics11060777
|View full text |Cite
|
Sign up to set email alerts
|

Survey on Carbapenem-Resistant Bacteria in Pigs at Slaughter and Comparison with Human Clinical Isolates in Italy

Abstract: This study is focused on resistance to carbapenems and third-generation cephalosporins in Gram-negative microorganisms isolated from swine, whose transmission to humans via pork consumption cannot be excluded. In addition, the common carriage of carbapenem-resistant (CR) bacteria between humans and pigs was evaluated. Sampling involved 300 faecal samples collected from slaughtered pigs and 300 urine samples collected from 187 hospitalised patients in Parma Province (Italy). In swine, MIC testing confirmed resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 73 publications
0
1
0
Order By: Relevance
“…Since swine meat and products might be potential sources of human exposure to resistant commensal and pathogenic bacteria [14] monitoring the trends of AMR at the farm [7,13] and slaughter [15,16] levels is necessary to identify emerging trends to prevent human infections caused by foodborne antimicrobial-resistant bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Since swine meat and products might be potential sources of human exposure to resistant commensal and pathogenic bacteria [14] monitoring the trends of AMR at the farm [7,13] and slaughter [15,16] levels is necessary to identify emerging trends to prevent human infections caused by foodborne antimicrobial-resistant bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of foodborne transmission of MRSA has been reported by several authors [121,122]. Similarly, Bonardi et al (2022) found a genetic relationship between swine and human isolates, although no direct epidemiological link was demonstrated [123].…”
Section: Antimicrobial Resistance In Staphylococcus Aureusmentioning
confidence: 90%
“…Intensive farming has frequently been associated with the excessive use of antimicrobials and drug-resistant microorganisms isolated from food-producing animals that can be transmitted to humans via direct contact with animals or ingestion of derived food products (9). By 2030, global antimicrobial use from human, terrestrial, and aquatic food-producing animal sectors will reach 236,757 tons annually, with an estimated proportion of terrestrial food-producing animal use of 174,549 tons, representing 73.7% of the global consumption of antimicrobials (55).…”
Section: Occurrence Of Carbapenem-producing Bacteria In Terrestrial F...mentioning
confidence: 99%
“…This intensive use of antibiotics creates selective pressure for the emergence of antimicrobial resistance among farmers and the environment. In addition, antibiotics continue to be used in livestock production as prophylaxis and animal growth support (9), which may lead to the emergence of antimicrobial resistance.…”
Section: Occurrence Of Carbapenem-producing Bacteria In Terrestrial F...mentioning
confidence: 99%